ANALISIS DER DAN NPM PADA PERUSAHAAN SEKTOR KOSMETIK DAN RUMAH TANGGA YANG TERDAFTAR DI BEI - Nurchairunisyah Nuchairunisyah; Nafisah Nurulrahmatiah (STKIP Persada Khatulistiwa Sintang, 2022)
Cosmetics and household sub-sector companies are part of one of the consumer goods industry sectors listed on the IDX. This study aims to determine and analyze DER and NPM in sub-sector companies listed on the IDX. This type of research is descriptive using quantitative data types from secondary data sources. The research instrument is a list of tables in the form of financial reports containing data on total liabilities, capital, profits and sales in 2016-2020 which can be accessed via the webside www.idx.co.id. The population used in this study are all cosmetic and household sub-sector companies listed on the IDX from 2016-2020 as many as 7 companies. The samples in this study were 4 cosmetic and household sub-sectors listed on the Indonesian stock exchange from 2016-2020. The sampling technique used in this study is a purposive sampling technique. Data collection techniques using documentation and literature study. Techniques of data analysis using the one sample t test. The results of the study stated that the DER in the cosmetics and household sub-sector was in the bad category while the NPM in the cosmetics and household sub-sector was in the very good category